Global Quality Assurance in Nursing Education: ACEN Standards and International Accreditation (International Journal of Nursing Education, 2026)
Accreditation plays a critical role in ensuring the quality, credibility, and continuous improvement of nursing educationprograms worldwide. This article examines the role of accreditation in nursing education, with an emphasis on qualityassurance, public trust, and the promotion of ongoing program evaluation and enhancement. Particular attention is givento the benefits of international nursing accreditation for students, faculty, institutions, employers, and communities ofinterest, including improved educational quality, enhanced global recognition, and increased mobility of graduates.The article also addresses challenges associated with international accreditation, such as time, financial costs, and thesustained commitment required to maintain compliance with accreditation standards. Additionally, the work highlightsinternational accreditation efforts led by the Accreditation Commission for Education in Nursing (ACEN), outlining itsglobal reach, comprehensive Standards and Criteria, and support for programs seeking this recognition. The article alsoprovides an overview of the ACEN Standards and Criteria as applied in international contexts, illustrating how global qualitybenchmarks are implemented while respecting local regulatory and cultural frameworks.By applying consistent, globallyrelevant standards while allowing programs to reflect local regulatory and cultural contexts, international accreditationsupports excellence in nursing education and contributes to the preparation of competent, ethical, and practice-readynurses worldwide.
Keywords: Accreditation, Quality, Standards